Site Fidelity, Annual Return Rate, Site Switching and Movement of Shorebirds Wintering in Thane Creek, West Coast of India, with Conservation Implications - Prabhu, Mrugank V.; Bajaru, Sameer; Sankpal, Shashank; Balachandran, S.; Khot, Rahul; Apte, Deepak (Journal of the Bombay Natural History Society (JBNHS), 2022)
Shorebird populations have been declining globally due to human disturbances. One such affected site is the Mumbai Metropolitan Region (MMR), particularly Thane Creek, India. Thane Creek has been under grave threat from urbanisation. Though a critical shorebird wintering site on the west coast of India and Central Asian Flyway (CAF), it has been neglected. Hence, we undertook this study to examine the site fidelity, annual return rate, site switching, and movement of wintering shorebirds in Thane Creek to understand their migration ecology and suggest conservation management actions. We ringed 10,575 shorebirds belonging to 49 species from five high-tide roosting sites around Thane Creek during 2014–15 and 2018–21. A total of 1,013 recaptures and re-sightings of 196 individuals belonging to 19 species were recorded. Site fidelity estimates ranged between 10.22% (n=274) for Terek Sandpiper Xenus cinereus to 0.41% (n=245) for Little Stint Calidris minuta. Annual return rates were highest for Common Redshank Tringa totanus (16.71%, n=383) and Common Sandpiper Actitis hypoleucos (10%, n=30), whereas lowest for Little Stint (0.12%, n=1606). We found that site fidelity was usually higher than site switching (less than 2% for most species) reflecting the strong site fidelity. The roost site fidelity variation seemed more likely to be driven by the roosting site’s quality, age or sex of species, capturing efforts, and human and predator disturbances. Our findings suggested that TSC (Training Ship Chanakya), Panje wetlands, and BPS (Bhandup Pumping Station) saltpans and mangrove were critical sites for shorebird conservation in Thane Creek. Currently, these sites are facing threats from landfilling, excavation, blocking tidal water movement, mangrove incursion, fishing, recreational and commercial development, electric power transmission lines, and bird watching and photography. We recommend the following measures should be taken at high-tide roosting sites to improve shorebird conservation: Regulating blocking of tidal water, water level, fishing, and birdwatching and photography; active management of mangrove incursion; prohibiting mangrove and tree plantation, landfilling, excavation, recreational and commercial development; and the roosting sites should be included in or made legally associated with Thane Creek Flamingo Sanctuary.